2012
DOI: 10.4238/2012.september.3.2
|View full text |Cite
|
Sign up to set email alerts
|

CYP2E1 RsaI and 96-bp insertion genetic polymorphisms associated with risk for colorectal cancer

Abstract: ABSTRACT.We investigated a possible association between alcoholism, cigarette smoking, obesity and CYP2E1 RsaI and 96-bp insertion genetic polymorphisms with risk for colorectal cancer (CRC). Patients with CRC (70 women and 61 men) were matched for gender and age to 206 healthy controls. The mean age of the two groups was 62 years. Meat intake, cigarette smoking and alcohol drinking were assessed using a specific frequency questionnaire. The body mass index was also calculated. DNA was extracted from periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…The association highlighted by our meta-analysis between the CYP2E1 gene and colorectal cancer (CRC), head and neck cancer (HNC) and liver cell carcinoma (LLC) is supported by published data [33-39,44,121]. An additional literature search to evaluate our initial results revealed novel correlations of the gene combination CYP2E1 and GSTM1 with prostate cancer (PC) susceptibility, lung cancer (LC) and bladder cancer (UBC) as shown in Table 2[126-128].…”
Section: Resultssupporting
confidence: 77%
“…The association highlighted by our meta-analysis between the CYP2E1 gene and colorectal cancer (CRC), head and neck cancer (HNC) and liver cell carcinoma (LLC) is supported by published data [33-39,44,121]. An additional literature search to evaluate our initial results revealed novel correlations of the gene combination CYP2E1 and GSTM1 with prostate cancer (PC) susceptibility, lung cancer (LC) and bladder cancer (UBC) as shown in Table 2[126-128].…”
Section: Resultssupporting
confidence: 77%
“…Studies have also shown an association between the polymorphic genotype of CYP2E1 *5B ( CC )[10,27,32,33] and the polymorphic genotype of CYP2E1 *6 ( AA )[10,34] and increased SCRC risk in Caucasians. However, in other studies, these polymorphisms were not associated with SCRC[17,34-36].…”
Section: Discussionmentioning
confidence: 99%
“…The form of variant contains polymorphic base substitution sites in a region of the gene that is not transcribed but that appears to be involved in the transcriptional regulation of CYP2E1 expression [16,17]. However, there has been considered as one in vitro study, showing that the variant allele (-/-) increased expression of a reporter gene constructs [18].…”
Section: Introductionmentioning
confidence: 99%